The Role of Audit Committee Supervisory Quality: The Effect ff Stakeholder Pressure on The Quality of Sustainability Reporting - Jefry Prabowo; Sri Hastuti; Retno Yulianti (E-Jurnal Akuntansi, 2025)
This study aims to examine the effect of media exposure and investor pressure on the quality of sustainability reporting, as well as the role of audit committee oversight as a moderating variable in energy companies listed on the Indonesia Stock Exchange for the period 2021–2024. Data were obtained from annual reports and sustainability reports using purposive sampling, resulting in 268 samples. Multiple regression analysis with MRA testing was conducted. The results show that media exposure has a significant positive effect, while investor pressure has a negative effect. The role of audit committee oversight does not moderate the relationship between media exposure and sustainability reporting quality, but it does weaken the effect of investor pressure on sustainability reporting quality and can even change the direction of the coefficient to positive.